Comparison of Credit Risk Management Practices among Islamic and Public Commercial Bank’s in Pakistan - Iqbal, Muhammad Saeed; Sofi, Mohd Fikri (Superior University, 2023)
The main objective of this research is to explain credit risk management practices. Furthermore, this research evaluates credit risk management practices in Pakistani banks. It compares and evaluates the techniques used by Islamic and public commercial banks. Quantitative research methods were used in the present study. A total of 400 self-administrated questionnaires have been distributed among Pakistani employees of selected banks. SPSS version 24 has been used to analyze responses using correlation, regression, and t-tests. Study results showed that all variables are significantly correlated. Moreover, this study found a significant difference (p<0.5) of credit risk management practices include credit risk understanding, credit risk identification, credit risk assessment, credit risk monitoring and credit risk analysis, among Islamic and public commercial banks of Pakistan. It is concluded that this study results may help the banks to find the solutions that enable quality loan creation and growth as well as to determine the relationship among the theories, concepts, of credit score and credit policies both at country level and regional level. Hence, this study is assumed to be significant in indicating best practices and concept for practical lending to enhance the performance of credit management to all mangers and policy makers of the banks as well as to all financial institutions and banks